Aztec, Inca & Maya - Baquedano, Elizabeth; Zabé, Michel (London ; New York : DK Pub., 2005)
Chronicles the history, beliefs, and everyday lives of the ancient Aztec, Inca, and Maya peoples.
Includes index.
8.0
5-8
5-8
1050L
Keywords: Aztecs -- Juvenile literature; Mayas -- Juvenile literature; Incas -- Juvenile literature; Aztecs; Mayas; Incas; Indians of Mexico; Indians of Central America; Indians of South America; Aztecs; Mayas; Incas; Native Americans -- Mexico; Native Americans -- Central America; Native Americans -- South America